Women’s Rebellion against Patriarchal Society as Reflected in Ayu Utami’s Si Parasit Lajang and Pengakuan Eks Parasit Lajang - Anastasia Sidharta (Journal of Education Papua Baru, 2024)
This study examines the influence of patriarchal culture in Indonesia and the active response of feminist literary criticism through the analysis of Ayu Utami's novels "Si Parasit Lajang" and "Pengakuan Eks Parasit Lajang." Using qualitative research method, consisting of primary and secondary data such as bibliography and content analysis, the research reveals the resistance of women against the patriarchal society. The analysis indicates that the novels are an expression of gender equity and the struggles that women and other form of marginalized constituents in Indonesian society encounter. The novels endeavor not only to generate this comprehension of feminist ideas but also awake in women consciousness of their identity and a readiness to assert their identities. The results imply education reform, suggesting the integration of literary works into the approved program to test the students’ language proficiency and, in addition, to interest students in the complex situations illustrated in literature. In conclusion of this study, research can take steps forward in analytic skill improvement. Key words: women, rebellion, against, patriarchal, society, feminism